CONSUMER ACCEPTANCE TO CATFISH (Pangasius hypophthalmus) KAMABOKO USING THE PURPLE SWEET POTATO FLOUR (Ipomoea batatas var. Ayamuraski)TO SUBSTITUTE THE USE OF TAPIOCA FLOUR - Purnama Dewi Putri Wardani; Dewita Dewita; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
Abstract             This research aimed to determine the consumer acceptance to the catfish (Pangasius hypophthalmus) kamaboko using the purple sweet potato flour (Ipomoea batatas var. Ayamuraski)to substitute the use of tapioca flour.The research method used in this research was experimental method. The experiment  wasconducting by producing kamaboko catfishby adding the purple sweet potato flourto substitute the use of tapioca flour at varied amount to every 30 gstotal weight offlourused. It consisted of four varied composition, namely: 30 gs tapioca flour and 0 g purple sweet potato flour (TJ0), 20 gs tapioca flour and 10 gs purple sweet potato flour (TJ1), 10 gs tapioca flour and 20 gs purple sweet potato flour (TJ2), and 0 g tapioca flour and 30 gs purple sweet potato flour (TJ3). The results showed that the best catfish kamaboko was produced by the using of 10 gs tapioca flour and 20 gs purple sweet potato flour (TJ2). The best product of kamaboko was mostly preferred by consumer at 92,5% for its consistence, 91,25% for its aroma ; 87,50% for its taste and 96,25% for its texture. The score anava were 3,23; 3,19; 3,20 and 3,25 respectively. Based on proximate analysis, kamaboko which mostly preferred by consumerwas containing moisture 66,69%, ash 2,14%, protein 15,84%, fat 7,05% and fiber 2,69%. Keywords: Kamaboko, catfish, tapioca flour, purple sweet potato flour, consumer              acceptance